Study and implementation of an advanced transceiver for 5G - Mendes, Diogo Roque (2019)
With the years passing by, the users of mobile networks present higher needs and demands when it comes to e ective download and upload data rates. The fth generation of mobile communications assumes the concretization of binary rates above 1 Gbps to be achieved by any ordinary user. To ful l this requirement, it was necessary to undertake a study and development of a system using the 4th Generation of Mobile Communications (4G) waveform to lessen the need for adding new modules and increasing the complexity of mobile network systems. The main goal is to develop an Orthogonal Frequency Division Multiplexing (OFDM) waveform simulator for 5th Generation of Mobile Communications (5G) using Quadrature Amplitude Modulation (QAM), simulate its performance to compare with the theoretical one and perform laboratorial tests. In this study the channel estimation is carried out and we evaluated the performance of Bit Error Rate (BER) and Error Vector Magnitude (EVM) as study metrics and parallels the usual transmission loss models for indoor and free-space communications. The study and experiments end in resulting mobile uncoded and convolutional hard decision OFDM communications up to 5.9 Gbps of e ective data rate and the results and measurements were obtained inside the laboratory environment, with a signal carrier of 3.5GHz and 2dB of both antennas gain and 26dB of ampli er gain at distances up to 4 meters between the two antennas. The best result obtained considering the highest data rate achieved was a 256-QAM uncoded OFDM communication at 5.9 Gbps on a 4 meters distance between antennas.